2020
DOI: 10.3389/fmed.2020.00231
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Diagnosis, and Treatment of COVID-19 in Hospitalized Patients: A Systematic Review of Case Reports and Case Series

Abstract: Introduction: The 2019 novel coronavirus (COVID-19) has been declared a public health emergency worldwide. The objective of this systematic review was to characterize the clinical, diagnostic, and treatment characteristics of hospitalized patients presenting with COVID-19. Methods: We conducted a structured search using PubMed/Medline, Embase, and Web of Science to collect both case reports and case series on COVID-19 published up to April 24, 2020. There were no restrictions regarding publication language. Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 103 publications
9
59
0
Order By: Relevance
“…COVID-19 is known for causing acute respiratory syndrome with nonspecific presenting symptoms characterized by fever, cough, chills, dyspnea, myalgia, and sore throat (Tahvildari et al, 2020). However, COVID-19 can also cause loss of smell (anosmia) and loss of taste (ageusia) early in the disease.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is known for causing acute respiratory syndrome with nonspecific presenting symptoms characterized by fever, cough, chills, dyspnea, myalgia, and sore throat (Tahvildari et al, 2020). However, COVID-19 can also cause loss of smell (anosmia) and loss of taste (ageusia) early in the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The immune response in SARS-CoV-2 patients occurs in two phases: Initially, when the disease is moderate, the immune cells eliminate the virus by producing primary cytokines, which may be beneficial for eliminating the virus but results in inflammation. During the second phase of more severe cases, SARS-CoV-2 patients exhibit significantly high cytokine levels or hyper-inflammation, and in some cases, the lungs become damaged (Figure 4; Azin et al, 2020;Shih-Hwa et al, 2020). Patients in this stage develop ARDS, and worsening damage to the lungs is a major challenge.…”
Section: Immune Responsementioning
confidence: 99%
“…et al, 2020;. A high level of IL-6 can suppress normal cell activation (Azin et al, 2020). Thus, a cytokine storm may help with the suppression of T-cells in SARS-CoV-2 patients (Puja et al, 2020).…”
Section: Immune Responsementioning
confidence: 99%
“…Shortness of breath, fever and dry cough were the most prevalent symptoms in our sample. Fever and cough had been reported as the most prevalent symptoms in several studies, including the Mexican population and severe cases (5,10,15,(17)(18)(19)). On the other hand, the third most prevalent symptom varies widely; for instance, a review found dyspnea prevalence of 53 -80%, and a series of fatal cases found in 70.6% (5,17).…”
mentioning
confidence: 99%
“…The copyright holder for this this version posted September 23, 2020. ; https://doi.org/10.1101/2020.09.21.20199117 doi: medRxiv preprint hypertension compared with diabetes (8,10). Nonetheless, in other populations hypertension has a much higher prevalence compared to diabetes (5,18). In two meta-analyses from the same work group (20,21), hypertension and diabetes were associated with poor outcomes in COVID-19.…”
mentioning
confidence: 99%